Management consultancy and humour in action and context - STURDY, Andrew (Institutional Knowledge at Singapore Management University, 2008)
Management consultancy has been one of fastest growing occupational sectors since the mid 1960s and currently generates worldwide revenues of over £100 billion. The huge expansion in consulting has meant that consultants have become key agents in the process of knowledge production. They act as conduits through which knowledge from a variety of sources is appropriated , transformed, and sometimes transferred into and from client organizations. They also legitimate or "rubber stamp" knowledge already held by their clients. Whether as employees or citizens, few of us can escape their influence.